FAKTOR PENENTU MINAT MENGGUNAKAN TEKNOLOGI NFC SEBAGAI SISTEM PEMBAYARAN (STUDI KASUS PENGGUNA KARTU KREDIT DI INDONESIA DENGAN MENGGUNAKAN PENDEKATAN ACCEPTANCE MODEL) - Syika Putri Nuraini; Meta Andriani (Universitas Multimedia Nusantara, 2020)
This study revisits the intention to use NFC payments in the context of credit cards. NFC is a system method that requires someone to make payments using a password without a card. In the background of this research problem, how Indonesian consumer acceptance of NFC system method. This study uses a descriptive research design with data collected through an online survey of sample credit users. Empirical data is then processed using SEM to be requested from the proposed hypothesis. The results of the conclusions of this study are the attitude towards the use of NFC, individual mobility, perceived compatibility, subjective norms have a positive effect on intention to use NFC payment, meanwhile perceived usefulness, perceived security, subjective norms have a positive effect on attitude toward the use of NFC payment, and Perceived ease of use has a positive effect on Perceived Usefulness Key Words: Credit Card, NFC, Payment System, Intention to Use, Acceptance Model.